Corporately-law problems of managing the activities of a legal entity (Journal of actual problems of jurisprudence, 2018)
The author considers in the article some issues of governing the activity of a legal entity. In particular, the author concentrates on features of corporate governance in such organisational-legal forms of legal entities as limited liability partnership and joint stock company. The special attention in the article is spared also to plenary powers and responsibility of organs of legal entity.With the development of market relations, a lot of business entities appeared in Kazakhstan. Legal entities are special subjects of law, recognized as such only from the position of law. The status of a legal entity allows solving many economic and managerial tasks. Through this form, entrepreneurial activity is realized, property (“proprietary”) interests of the participants of the legal entity are ensured, management of the affairs of other legal entities is conducted for various reasons. The convenience of this form is manifested, first of all, in limiting the liability of participants, in limiting the risk of property losses for participants of a legal entity.Key words: legal entity, joint stock company, liability, participant.